STEM Practices: A translational framework for large-scale STEM education design - Lowrie, Thomas; Leonard, Simon; Fitzgerald, Robert (EDeR. Educational Design Research, 2018)
Underpinned by the nation-wide Early Learning STEM Australia (ELSA) project, this practice illustration presents a design framework to respond to the challenges of scaling and sustaining a large design-based research project. The framework, known as STEM Practices Framework, is informed by work within the Learning Sciences which suggests that the interplay between project innovation and the wider educational reform priorities are critical to the sustainability and scalability of projects. The ELSA project responded to this by developing processes of developmental evaluation to parallel the design based research of the project. Emerging from that process was a design proposition that the object of the project, and the entire STEM education agenda, is not simply to improve educational practice, but to shift educational purpose. Specifically, the paper argues that STEM Practices represents a qualitative shift in purpose from the content bound traditions of science, technology, engineering and mathematics education towards developing a greater capacity to use practices in diverse STEM contexts. The STEM Practices Framework described here was developed to support educators and developers to implement the project innovations built on this understanding. The framework is in two parts: (1) an adaptation of Kemmis et al.’s (2014) practice architectures approach and the practice architectures that support and constrain those practices. (2) A heuristic for working with STEM practices in large scale implementation.